Exercise stress echocardiography in children and teenagers with congenital heart diseases. (14th October 2021) - Avesani, M; Calvo, G; Sirico, D; Castaldi, B; Reffo, E; Cerutti, A; Biffanti, R; Di Candia, A; Sabatino, J; Borrelli, N; Piccinelli, E; Fraisse, A; et al.
Abstract: Background: Exercise Stress Echocardiography (ESE) is currently applied to paediatric patients mainly to detect myocardial ischemia and few data is available for congenital heart diseases (CHDs). Purpose: The aim of this study is to describe the current application of ESE in our Departments. Methods: Data from patients who underwent ESE in our two centres were retrospectively analysed, as well as clinical management plans formulated based on ESEs results. Results: Fifty-five patients (median age 15 years) were included. Among them, 19 had been previously treated surgically, 6 percutaneously and 30 were under follow-up. Indications for ESE were: hypertension and/or evaluation of aortic arch gradient in patients treated surgically (5) or percutaneously (1) for aortic coarctation (ACo); aortic/subaortic gradient in bicuspid aortic valve (BAV) after balloon valvuloplasty (4), Ross (1), or under follow up (1); right ventricular and pulmonary valve function in Tetralogy of Fallot (3) and after percutaneous treatment of pulmonary atresia (1); atrio-ventricular valves gradient (1 for tricuspid dysplasia and 1 for left cor triatriatum); single ventricle function (1); pulmonary artery gradient (2) and myocardial ischemia (6) after Arterial Switch; rule out myocardial ischemia in coronary anomalies (4), chest pain (9), Kawasaki disease (KD 9), syncope (1) and in patients with ectopic beats under exercise (2); rule out dynamic obstruction in hypertrophic cardiomyopathy (HCM, 3). The exercise was maximal in 28 patients, with 2 of them having symptoms at the peak of exercise. In the other patients, peak heart rate ranged from 52% to 84% of targeted values. Mean exercise duration and reached Watts were 10 minutes and 112, respectively. Reasons for ending exercise were muscle fatigue in 25 patients and dyspnoea in 2 patients. No arrhythmia was detected. Clinical management changed in 10 of patients after ESE (20%), all having CHDs. Three patients underwent percutaneous interventions; 1 aortic balloon valvuloplasty, 1 stent dilation and 1 pulmonary valve replacement; 2 underwent surgery (1 aortic valve replacement and 1 subaortic membrane resection), 4 underwent further imaging including cardiac computed tomography (1), cardiac magnetic resonance (2) and cardiac catheterization (1); 1 received indication for restriction from intense physical activities. Conclusions: ESE has an important clinical role in patients with congenital heart diseases, impacting clinical management. FUNDunding Acknowledgement: Type of funding sources: None.